Biomechanics of human trabecular meshwork in healthy and glaucoma eyes via dynamic Schlemm's canal pressurization. (June 2022) - Karimi, Alireza; Rahmati, Seyed Mohammadali; Razaghi, Reza; Crawford Downs, J.; Acott, Ted S.; Wang, Ruikang K.; Johnstone, Murray
Highlights: Time-dependent viscoelastic mechanical properties of the TM/JCT/SC complex were calculated. Larger time-dependent shear moduli were calculated in the ECM of the glaucoma eyes. Fibrils in the glaucoma eyes exhibited stiffer mechanical response compared to the healthy eyes. Elastic material model unable to capture the dynamic time-dependent mechanical response of TM. TM/JCT/SC mechanical properties could serve as a new biomarker for glaucoma diagnosis. Abstract: Background and objective: The trabecular meshwork (TM) consists of extracellular matrix (ECM) with embedded collagen and elastin fibers providing its mechanical support. TM stiffness is considerably higher in glaucoma eyes. Emerging data indicates that the TM moves dynamically with transient intraocular pressure (IOP) fluctuations, implying the viscoelastic mechanical behavior of the TM. However, little is known about TM viscoelastic behavior. We calculated the viscoelastic mechanical properties of the TM in n   =   2 healthy and n   =   2 glaucoma eyes. Methods: A quadrant of the anterior segment was submerged in a saline bath, and a cannula connected to an adjustable saline reservoir was inserted into Schlemm's canal (SC). A spectral domain-OCT (SD-OCT) provided continuous cross-sectional B-scans of the TM/JCT/SC complex during pressure oscillation from 0 to 30 mmHg at two locations. The TM/JCT/SC complex boundaries were delineated to construct a 20-µm-thick volume finite element (FE) mesh. Pre-tensioned collagen and elastin fibrils were embedded in the model using a mesh-free penalty-based cable-in-solid algorithm. SC pressure was represented by a position- and time-dependent pressure boundary; floating boundary conditions were applied to the other cut edges of the model. An FE-optimization algorithm was used to adjust the ECM/fiber mechanical properties such that the TM/JCT/SC model and SD-OCT imaging data best matched over time. Results: Significantly larger short- and long-time ECM shear moduli ( p  = 0.0032), and collagen (1.82x) and elastin (2.72x) fibril elastic moduli ( p  = 0.0001), were found in the TM of glaucoma eyes compared to healthy controls. Conclusions: These findings provide additional clarity on the mechanical property differences in healthy and glaucomatous outflow pathway under dynamic loading. Understanding the viscoelastic properties of the TM may serve as a new biomarker in early diagnosis of glaucoma. Graphical abstract: Image, graphical abstract